2008
DOI: 10.1021/jp077275m
|View full text |Cite
|
Sign up to set email alerts
|

Defect Chemistry of Titanium Dioxide. Application of Defect Engineering in Processing of TiO2-Based Photocatalysts

Abstract: The present work brings together the concepts of defect chemistry and photoelectrochemistry in order to consider TiO2-based photosensitive oxide semiconductors as photocatalysts for water purification. This paper reports the most recent progress in the defect chemistry of TiO2 and its solid solutions with aliovalent ions forming donors and acceptors. The relationship between the defect-related properties, such as electrical and photocatalytic properties, are outlined. It is shown that reactivity, photoreactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
562
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(583 citation statements)
references
References 115 publications
16
562
0
5
Order By: Relevance
“…A number of studies 7,8,16,44,48,49,59 have already shown the importance of the lattice defects in conjunction with PCA either in the case of pristine or heterojunction catalysts, where they can be identied through optical properties. We have performed PL spectroscopy on the CSHJ nanobers (Fig.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
“…A number of studies 7,8,16,44,48,49,59 have already shown the importance of the lattice defects in conjunction with PCA either in the case of pristine or heterojunction catalysts, where they can be identied through optical properties. We have performed PL spectroscopy on the CSHJ nanobers (Fig.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
“…In connection to lattice defects, depending on the type and energetic location of the defect, their character is determined to capture either an electron or a hole, thereby delaying the recombination process. [1][2][3][4]6,[8][9][10][11][12][13] As a consequence, the captured or free charge carrier participates in photocatalytic activity (PCA), in which the catalysis occurs at the conduction band (CB), valance band (VB) and the defect site, if available on the surface. 4,8 Note that the defects form intermediate bands within the band gap, which allow visible light harvest especially in the case of wide band gap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,8,[15][16][17] The lattice defects connected to PCA are basically intrinsic (vacancies, interstitials, anti-site) or extrinsic (induced by impurities) in nature. 1,4,6,[8][9][10][11][12][13]15,18 However, it is rather hard, though intriguing, to determine which defect is more benecial for PCA, especially in the context of ZnO because controlling the defect density and maintaining a balance among various defect types is quite challenging. 15 On the other hand, dominant defect density can compromise optical quality; nevertheless, it increases PCA, as recently reported by us.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors, making defects in photocatalysts has been found to be an effective method for improving the activity via changing the charge transfer and band structure. 16,17 Especially, oxygen-vacancy can serve as photoinduced charge traps and modify the band structure of semiconductor photocatalysts, which is conductive to the enhanced photocatalytic activity. [18][19][20] The light absorption range of semiconductor materials can be enhanced or expanded by introducing oxygen vacancies, which results in the extended light absorption spectra and band gap narrowing.…”
Section: Introductionmentioning
confidence: 99%